2017
DOI: 10.1121/1.4987457
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of arctic ambient noise environment

Abstract: Historically, ambient noise in arctic ocean is predominately produced by diffuse thermal ice cracking events or ice ridge grinding. Isotropic, range-distributed noise sources models are typically utilized to simulate this environment. However, the presence of the Beaufort Lens and changes in the arctic climate have altered its ambient noise environment. Specifically, the new noise environment consists mostly of ice cracking events which occur at discrete ranges and bearings. As a result, these noise models may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Moreover, contribution of Cs to the VB and CB was negligible, while FA contribution was much more pronounced, as shown by the joint experimental and theoretical investigations. 16 The increased density of states in the presence of organic cations decrease the energy level spacing, and hence, increase the NAC. As a result, MAPbI 3 and FAPbI 3 showed faster carrier cooling than CsPbI 3 , Fig.…”
Section: Hot Carrier Fluorescence and Coolingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, contribution of Cs to the VB and CB was negligible, while FA contribution was much more pronounced, as shown by the joint experimental and theoretical investigations. 16 The increased density of states in the presence of organic cations decrease the energy level spacing, and hence, increase the NAC. As a result, MAPbI 3 and FAPbI 3 showed faster carrier cooling than CsPbI 3 , Fig.…”
Section: Hot Carrier Fluorescence and Coolingmentioning
confidence: 99%
“…14 To further improve PSCs performance towards the Shockley-Queisser efficiency limit, it is imperative to eliminate all possible nonradiative recombination pathways. Numerous strategies have been devoted to this topic, including chemical surface treatment, 15 compositional engineering, 16 exposure to environmental factors such as oxygen, moisture, and light, 17 reduction of dimensionality, 18 variations in temperature, pressure, and electric field, [19][20][21] and ferroelectric polarization tuning. 10 Many types of time-resolved ultrafast spectroscopies, including photoluminescence (PL), terahertz (THz), and transient absorption (TA) measurements, have been utilized to study evolution of charge carriers, exemplifying these realistic factors in PSCs and providing huge amounts of data that are typically interpreted phenomenologically.…”
Section: Introductionmentioning
confidence: 99%
“…Their group demonstrated as well in their study that HCs experience longer time at higher excited states to return (i. e., relax or cool) to the band edge and made compare to the HCs brought forth through the low excitation energy. [51] In 2017, Li et al showcased in their reported studies that the HC relaxation kinetics is deaccelerated on the account of NC size dependency and enhancement of the efficient HC extraction into the device. This paves the way for the potential applications of the LHPNCs in the sphere of HC photovoltaic devices (e. g., solar cells).…”
Section: Introductionmentioning
confidence: 99%
“…75 However, the property can be further refined by chemical doping of cations such as FA, which has the fastest hot cooling relaxation. 76 3. CsPbI 3 PQD Synthesis, Post-treatment mechanism and QD Ink…”
Section: Multi Exciton Generationmentioning
confidence: 99%